Anti-thrombosis effect of diosgenyl saponins in vitro and in vivo - Zhang, R.; Huang, B.; Du, D.; Guo, X.; Xin, G.; Xing, Z.; Liang, Y.; Chen, Younan; Chen, Q.; He, Y.; Huang, W. (2013)
Thrombosis in coronary or cerebral arteries is the major cause of morbidity and mortality worldwide. Diosgenin and total steroidal saponins extracted from the rhizome of Dioscorea zingiberensis C.H. Wright are demonstrated to have anti-thrombotic activity. However, few studies describe the anti-thrombotic activity of the diosgenyl saponin monomer. In the present study, a simple and convenient method for the preparation of a new disaccharide saponin, diosgenyl β-d-galactopyranosyl-(1 → 4)-β-d-glucopyranoside (3), is described. We evaluated the anti-thrombotic effects of diosgenin and four diosgenyl saponins by measuring the bleeding time; the results showed that compound 3 exhibits outstanding efficiency in prolonging the bleeding time. Furthermore, we assessed whether compound 3 could alter platelet aggregation in vitro and in vivo. In addition, activated partial thromboplastin time (APTT), thrombin time (TT), prothrombin time (PT), coagulation factors and protection rate in mice were measured to evaluate the anti-thrombotic effect of compound 3. The results show that compound 3 inhibited platelet aggregation, prolonged APTT, inhibited factor VIII activities in rats, and increased the protection rate in mice in a dose-dependent manner. Taken together, these findings suggested that diosgenyl saponins, especially compound 3, had anti-thrombotic activity. It may execute anti-thrombotic activity through inhibiting factor VIII activities and platelet aggregation.